PENGARUH MOTIVASI AWAL KULIAH BAGI MAHASISWA STKIP WIDYA YUWANA TERHADAP SEMANGAT PELAYANAN DI LINGKUNGAN - Bonaventura Praba Caraka; Agustinus Supriyadi (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Motivation is a conscious effort, which comes from within and outside of a person. Motivation is affecting a person's behavior so that he moved his heart to act to do something to achieve a certain result or goal. The call to be a catechist must be well motivated and not just looking for a position. This motivation is also needed by students of STKIP Widya Yuwana, as a potential catechist. The issues that arise are: whether the students of STKIP Widya Yuwana have pure motivation from inside themself as catechist? Are their motivations fixed or changed? Do they have the motivation to serve? How far the initial motivation to enter college to give influence for students of STKIP Widya Yuwana? How does motivation have an impact on pastoral care, which is the duty and responsibility of students of STKIP Widya Yuwana, as a potential catechist?Based on the problem, the purpose of this research is to see how far the influence of early motivation for college students of STKIP Widya Yuwana to the spirit of service in the environment.Through questionnaires to 48 respondents using quantitative research methods, it was found that most of the students admitted that there was an influence between the initial motivation to enter the lecture toward the pastoral practice in the environment, but the initial motivation of the students as candidates for catechism and/religious teachers needs to be refined so that students seriously answer the call of his life as a catechist candidate, not just to pursue offers that offer a position or salary alone. Thus, the coaching of these students needs to get the attention of many parties.